The Establishment of ‘Musicology Corner’ at the Sir Ponnampalam Ramanathan Faculty of Performing and Visual Arts Library - Poologanathan, P. (Library, University of Jaffna, 2024)
The Sir Ponnampalam Ramanathan Faculty of Performing and Visual Arts (SPRFPVA) Library is one of the seven branch libraries under the Library system of the University of Jaffna, serving over 700 students and 70 staff members. Despite having a collection of 1,500 non-book materials (such as CDs and DVDs) related to musicology, the library's existing infrastructure and technological facilities were insufficient, rendering these valuable resources largely inaccessible. Furthermore, the library lacked an appropriate space where students and faculty could effectively engage with resources, particularly for learning from live performance recordings and accessing online storage. These gaps in accessibility necessitated the establishment of ‘Musicology Corner’ at the SPRFPVA Library project, which aimed to enhance the infrastructure, thereby enabling the effective use of these resources. The project was funded with LKR 16.53 million from the Kandiah Karthigasen Tamil Music Trust Fund, with the primary objective of transforming the library into a more conducive environment for accessing and utilizing non-book materials.
Keywords: Musicology; Visual arts; SPRFPVALibrary; Infrastructure